Pengaruh Kepatuhan Pelaporan Keuangan, Sistem Pengendalian Internal, Whistleblowing System, dan Good Corporate Governance Terhadap Pencegahan Fraud Pengelolaan Dana Desa (Studi pada Desa di Kecamatan Pandaan) - Surya Saida; Maslichah Maslichah; Dewi Diah Fakhriyyah (Universitas Islam Malang, 2023)
This study aims to empirically examine the effect of financial reporting compliance, internal control systems, whistleblowing systems and good corporate governance on the prevention of village fund management fraud in Pandaan District, Pasuruan Regency. This research is a quantitative research, the source of data in this study using primary data obtained through distributing questionnaires. The sampling technique in this study used a purposive sampling technique, so that a sample of 79 respondents was obtained consisting of village heads, village secretaries, heads of planning affairs, heads of general affairs, heads of financial affairs, heads of development affairs in 14 villages in Pandaan District, Pasuruan Regency. The results of this study indicate that compliance with financial reporting, internal control systems, and the whistleblowing system have a positive effect on preventing fraud in managing village funds. Meanwhile, good corporate governance has no effect on preventing fraud in managing village funds.Keywords: Financial reporting compliance, internal control system, whistleblowing system, good corporate governance, fraud prevention